Spelling Interventions for Students Who Show Signs of Dyslexia - Caitlin N. Gritz (Networks: An Online Journal for Teacher Research, 2020)
This action research examines the impact of spelling interventions for students who show signs of dyslexia. The action research also shows how using growth mindset can help students with characteristics typical of low self-esteem. Students learned a new spelling pattern weekly and a growth mindset lesson to teach students how to have a growth mindset rather than a fixed mindset related to spelling skills. A pre-spelling inventory test and a post-spelling inventory test were compared to see that word study activities help students remember specific spelling patterns.
Keywords: Dyslexia; spelling; intervention; growth mindset